Territórios de organização política e lutas sociais: MTST e o povo sem medo do capão (2016-2019) - Rocha, Luciano Marcelino da (2022)
This research investigates the struggle for housing in the region of Capão Redondo taking it is a history of the struggle strategies of the Homeless Wokers Movement (MTST), in a network of action with de Povo Sem Medo Front. Located in the Conj. Hab. Jardim São Bento. The occupation emerged as a strategy to mobilize the MTST to deal with the dismantling of social and labor rights through a coalition of the progresive camp, which sought to respond to the advances of conservatism after the 2016 coup. The analysis starts fron a perspective of Social History in dialogue with the bibliographies that address the theme. With this focus, which we seek to understand, how its social actors and actresses reinvent politics in their relations with institutional spaces, building social struggles within their territories and beyond them. The work methodology dialogues with a theoretical conception that considers the role of culture in social movements, as a means of producing new meanings in collective action ments (THOMPSOM, 1987). The sources of the survey are the minutes of the occupation meeting that registered its actions in the year 2017; and two short film documentaries produced in 2016, which portrayed the daily life of the occupation and the memories of the struggle for housing in the neighborhood. To compose our documental corpus, in addition to the field study with “participatory research”, we analyzed some secondary sources that helped us to map the occupation actions up to the time frame proposed for this study